Alcaeus fr. 140.9 Voigt: the Unsolved Problem of the Text - Sergey A. Stepantsov (Studia Litterarum)
The author examines two variant readings in Alcaeus fr. 140 Voigt, a well-known poem listing pieces of arms. These two variants in line 9 are: ἔρκος (direct tradition represented by a papyrus fragment) and ἄρκος (from the quotation in Athenaeus). The word in question is used in the expression describing greaves: ἔρκος/ἄρκος ἰσχύρω βέλεος “a (de)fence against the arrow’s might”. A brief history of these variants in Alcaeus’ editions is outlined. The variant ἔρκος, attested by the papyrus, is supported by Homeric usage of ἕρκος in some parallel constructions of the Iliad, where it is used to describe means of defense. This variant is preferred in modern editions of Alcaeus’ fragments, including those by E.-M. Voigt (1971) and G. Liberman (1999). However, ἄρκος of the indirect tradition is a lectio difficilior and apparently has no less rights to be included in the fragment. Unlike ἄρκος, ἔρκος could have been a result of banalisation of the text (even as early as before the 2 nd century AD). Besides, ἄρκος fits in the context quite well, as one can infer from the usage of the word in later poets Nicander and Oppian, and probably by Alcaeus himself in fr. 396 Voigt.